CONTRIBUTIONS TO THE EDUCATION AND DEVELOPMENT OF AMBIDEXTERITY TO STUDENTS IN SECONDARY SCHOOL THROUGH MEANS SPECIFIC TO MOVEMENT GAMES - Beligan Ionuț; Benedek Florian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Movement games have a major importance for students in general and for secondary school students in particular. Through their specific content they form socio-psycho-molitic abilities of selfevoluation and the value of ones personality. Games have an important role in developing ones willingness its qualities. 'The effort of willingness is present in any human activity facilitating overcoming external or internal obstacles which can occur throughout a specific activity'.[3] Movement games offer the possibility to educate such qualities and require both physical and pshychic effort. Thus, movement games are complex exercises that have implications on humans personality and its different components (intellectual, affective and volitional). The purpose of these activities is to complete the activities organized by the school system.